Extensions 1→N→G→Q→1 with N=D4 and Q=C22×S3

Direct product G=N×Q with N=D4 and Q=C22×S3
dρLabelID
C22×S3×D448C2^2xS3xD4192,1514

Semidirect products G=N:Q with N=D4 and Q=C22×S3
extensionφ:Q→Out NdρLabelID
D41(C22×S3) = C2×S3×D8φ: C22×S3/D6C2 ⊆ Out D448D4:1(C2^2xS3)192,1313
D42(C22×S3) = C2×D8⋊S3φ: C22×S3/D6C2 ⊆ Out D448D4:2(C2^2xS3)192,1314
D43(C22×S3) = S3×C8⋊C22φ: C22×S3/D6C2 ⊆ Out D4248+D4:3(C2^2xS3)192,1331
D44(C22×S3) = C22×D4⋊S3φ: C22×S3/C2×C6C2 ⊆ Out D496D4:4(C2^2xS3)192,1351
D45(C22×S3) = C2×D4⋊D6φ: C22×S3/C2×C6C2 ⊆ Out D448D4:5(C2^2xS3)192,1379
D46(C22×S3) = C22×D42S3φ: trivial image96D4:6(C2^2xS3)192,1515
D47(C22×S3) = C2×D46D6φ: trivial image48D4:7(C2^2xS3)192,1516
D48(C22×S3) = C2×S3×C4○D4φ: trivial image48D4:8(C2^2xS3)192,1520
D49(C22×S3) = C2×D4○D12φ: trivial image48D4:9(C2^2xS3)192,1521
D410(C22×S3) = S3×2+ 1+4φ: trivial image248+D4:10(C2^2xS3)192,1524

Non-split extensions G=N.Q with N=D4 and Q=C22×S3
extensionφ:Q→Out NdρLabelID
D4.1(C22×S3) = C2×D83S3φ: C22×S3/D6C2 ⊆ Out D496D4.1(C2^2xS3)192,1315
D4.2(C22×S3) = D813D6φ: C22×S3/D6C2 ⊆ Out D4484D4.2(C2^2xS3)192,1316
D4.3(C22×S3) = C2×S3×SD16φ: C22×S3/D6C2 ⊆ Out D448D4.3(C2^2xS3)192,1317
D4.4(C22×S3) = C2×Q83D6φ: C22×S3/D6C2 ⊆ Out D448D4.4(C2^2xS3)192,1318
D4.5(C22×S3) = C2×D4.D6φ: C22×S3/D6C2 ⊆ Out D496D4.5(C2^2xS3)192,1319
D4.6(C22×S3) = C2×Q8.7D6φ: C22×S3/D6C2 ⊆ Out D496D4.6(C2^2xS3)192,1320
D4.7(C22×S3) = SD1613D6φ: C22×S3/D6C2 ⊆ Out D4484D4.7(C2^2xS3)192,1321
D4.8(C22×S3) = S3×C4○D8φ: C22×S3/D6C2 ⊆ Out D4484D4.8(C2^2xS3)192,1326
D4.9(C22×S3) = SD16⋊D6φ: C22×S3/D6C2 ⊆ Out D4484D4.9(C2^2xS3)192,1327
D4.10(C22×S3) = D815D6φ: C22×S3/D6C2 ⊆ Out D4484+D4.10(C2^2xS3)192,1328
D4.11(C22×S3) = D811D6φ: C22×S3/D6C2 ⊆ Out D4484D4.11(C2^2xS3)192,1329
D4.12(C22×S3) = D8.10D6φ: C22×S3/D6C2 ⊆ Out D4964-D4.12(C2^2xS3)192,1330
D4.13(C22×S3) = D84D6φ: C22×S3/D6C2 ⊆ Out D4488-D4.13(C2^2xS3)192,1332
D4.14(C22×S3) = D85D6φ: C22×S3/D6C2 ⊆ Out D4488+D4.14(C2^2xS3)192,1333
D4.15(C22×S3) = D86D6φ: C22×S3/D6C2 ⊆ Out D4488-D4.15(C2^2xS3)192,1334
D4.16(C22×S3) = S3×C8.C22φ: C22×S3/D6C2 ⊆ Out D4488-D4.16(C2^2xS3)192,1335
D4.17(C22×S3) = D24⋊C22φ: C22×S3/D6C2 ⊆ Out D4488+D4.17(C2^2xS3)192,1336
D4.18(C22×S3) = C24.C23φ: C22×S3/D6C2 ⊆ Out D4488+D4.18(C2^2xS3)192,1337
D4.19(C22×S3) = SD16.D6φ: C22×S3/D6C2 ⊆ Out D4968-D4.19(C2^2xS3)192,1338
D4.20(C22×S3) = C2×D126C22φ: C22×S3/C2×C6C2 ⊆ Out D448D4.20(C2^2xS3)192,1352
D4.21(C22×S3) = C22×D4.S3φ: C22×S3/C2×C6C2 ⊆ Out D496D4.21(C2^2xS3)192,1353
D4.22(C22×S3) = C2×Q8.13D6φ: C22×S3/C2×C6C2 ⊆ Out D496D4.22(C2^2xS3)192,1380
D4.23(C22×S3) = C12.C24φ: C22×S3/C2×C6C2 ⊆ Out D4484D4.23(C2^2xS3)192,1381
D4.24(C22×S3) = C2×Q8.14D6φ: C22×S3/C2×C6C2 ⊆ Out D496D4.24(C2^2xS3)192,1382
D4.25(C22×S3) = D12.32C23φ: C22×S3/C2×C6C2 ⊆ Out D4488+D4.25(C2^2xS3)192,1394
D4.26(C22×S3) = D12.33C23φ: C22×S3/C2×C6C2 ⊆ Out D4488-D4.26(C2^2xS3)192,1395
D4.27(C22×S3) = D12.34C23φ: C22×S3/C2×C6C2 ⊆ Out D4488+D4.27(C2^2xS3)192,1396
D4.28(C22×S3) = D12.35C23φ: C22×S3/C2×C6C2 ⊆ Out D4968-D4.28(C2^2xS3)192,1397
D4.29(C22×S3) = C2×Q8○D12φ: trivial image96D4.29(C2^2xS3)192,1522
D4.30(C22×S3) = C6.C25φ: trivial image484D4.30(C2^2xS3)192,1523
D4.31(C22×S3) = D6.C24φ: trivial image488-D4.31(C2^2xS3)192,1525
D4.32(C22×S3) = S3×2- 1+4φ: trivial image488-D4.32(C2^2xS3)192,1526
D4.33(C22×S3) = D12.39C23φ: trivial image488+D4.33(C2^2xS3)192,1527

׿
×
𝔽